Re-grounding the city with Polanyi: From urban entrepreneurialism to entrepreneurial municipalism. (September 2020) - Thompson, Matthew; Nowak, Vicky; Southern, Alan; Davies, Jackie; Furmedge, Peter
Conventional approaches to local economic development are failing to address deepening polarisation both within and between city regions across advanced capitalist economies. At the same time, austerity urbanism, particularly in the UK, presents challenges for urban authorities facing reduced budgets to meet increased demands on public services. Municipalities are beginning to experiment with creative responses to these crises, such as taking more interventionist and entrepreneurial roles in developing local economies, generating alternative sources of revenue or financialising existing assets. Rooted in a Polanyian perspective and building on the concepts of the entrepreneurial state and grounded city, we identify an embryonic alternative approach – what we call 'entrepreneurial municipalism' – as a policy pathway towards resolving enduring socioeconomic problems where neoliberal urban-entrepreneurial strategies have failed. We situate entrepreneurial municipalism as one strand in an assemblage of new municipalist interventions, between radical urban social movements and more neoliberal strategies such as financialised municipal entrepreneurialism. Drawing on original research on the Liverpool City Region, we explore how local authorities are working with social enterprises to harness place-based assets in ways which de-commodify land, labour and capital and re-embed markets back into society. Finally, we draw upon Polanyi as our guide to disentangle differences in approach amongst divergent forms of municipalist statecraft and to critically evaluate entrepreneurial municipalism as a possible trajectory towards the grounded city.